2022
DOI: 10.1101/gr.275831.121
|View full text |Cite
|
Sign up to set email alerts
|

TP53-inducible putative long noncoding RNAs encode functional polypeptides that suppress cell proliferation

Abstract: Polypeptides encoded by long non-coding RNAs (lncRNAs) are a novel class of functional molecules. However, whether these hidden polypeptides participate in the TP53 pathway and play a significant biological role is still unclear. Here, we discover that TP53-regulated lncRNAs encode peptides, two of which are functional in various human cell lines. Using ribosome profiling and RNA-seq approaches in HepG2 cells, we systematically identified more than 300 novel TP53-regulated lncRNAs and further confirmed that fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
0
5
0
1
Order By: Relevance
“…To demonstrate the utility of NAP-seq-NGS for identifying previously uncharacterized napRNAs compared to the GENCODE database (human release 30 and mouse release 23) 25 , in different cells and under different conditions, we further profiled the transcriptomes of 3 different stress responses (poly (I:C), adriamycin (ADR), and CoCl 2 ) in human HepG2 cells and 4 different myoblast differentiation stages in the mouse skeletal muscle cell line C2C12, as well as the abovementioned three cell lines. In these stress responses, poly (I:C) mimics double-stranded RNA to induce the activation of immune response 26 ; ADR causes DNA damage, triggering cells to activate their DNA damage repair machinery 27 , 28 ; CoCl 2 artificially induces hypoxia 29 , which has allowed the characterization of the hypoxia response at the cellular, biochemical and molecular levels 30 . Moreover, we developed a computational tool, napSeeker, to determine the full-length sequences of napRNAs from total NAP-seq data (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the utility of NAP-seq-NGS for identifying previously uncharacterized napRNAs compared to the GENCODE database (human release 30 and mouse release 23) 25 , in different cells and under different conditions, we further profiled the transcriptomes of 3 different stress responses (poly (I:C), adriamycin (ADR), and CoCl 2 ) in human HepG2 cells and 4 different myoblast differentiation stages in the mouse skeletal muscle cell line C2C12, as well as the abovementioned three cell lines. In these stress responses, poly (I:C) mimics double-stranded RNA to induce the activation of immune response 26 ; ADR causes DNA damage, triggering cells to activate their DNA damage repair machinery 27 , 28 ; CoCl 2 artificially induces hypoxia 29 , which has allowed the characterization of the hypoxia response at the cellular, biochemical and molecular levels 30 . Moreover, we developed a computational tool, napSeeker, to determine the full-length sequences of napRNAs from total NAP-seq data (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that following p53 activation, 380 altered lncRNAs were identified in liver HepG2 cells ( 49 ). We determined that compared with background lncRNAs, a significantly ( P = 1.27 × 10 −31 ; hypergeometric test) higher proportion of our predicted p53-effector lncRNAs overlapped with these altered lncRNAs, increasing confidence that our identified lncRNAs are core p53 targets.…”
Section: Resultsmentioning
confidence: 99%
“…The 5′ portion of LARP1B mRNA is heavily bound by ribosomes through analyzing available ribosome profiling sequencing (Ribo‐seq) data from HCC cell lines (GSE125757, GSE128320, and GSE147840) (Figure S5b , Supporting Information). [ 53 , 54 , 55 ] One possibility is that LARP1B mRNA is actively involved in translation, and the HNRNPD sites present in its 5′ are thus not available for HNRNPD binding.…”
Section: Resultsmentioning
confidence: 99%